PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAINEGERI SIPIL (Studi pada Unit Pelayanan Teknis Daerah Panti Sosial Se-Pulau Lombok) - Endang Sri Wahyuni (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This research is aimed at determining the effect of work motivation, satisfaction and organizational commitment on the performance of civil servant district unit of social home service in Lombok. This research is causal associative study with 181 civil servants in all social homes on Lombok as the population. The samples are 64 civil servant selected through Slovin formula. The data were collected through questionnaires distributed to the respondents. The data were analyzed with Multiple Linear Regression Analysis.  The research showed that work motivation has no significant effect on work performance, work satisfaction has no significant effect on the performance of the civil servant, and the organizational commitment has no significant effect on the work performance of the civil servant in all UPTD (District Unit of Service) in all Lombok districts.Keyword: organizational commitment, work satisfaction, work motivation, employees’ performance.